A Mixed Method Study Investigating the Impact of Talking about Patients' Internet Use on Patient-Reported Outcomes. Issue 9 (2nd September 2018) - Sanders, Remco; Linn, Annemiek J.
Abstract : This study aims to propose and test a model that provides a more comprehensive understanding of the impact of discussing online health information on patient outcomes. By combining survey data ( N = 160) and qualitative analysis of video recordings of consultations ( N = 165) with structural equation modeling, this study explores: (1) whether patients and health-care providers talk about online medical information and (2) the impact of talking about online medical information on patient outcomes (patient satisfaction, recall of medical information, and medication adherence). Results show that more than half of the patients searched online prior to their consultation. In about half of these consultations (46.81%), the online information was discussed. Patients were more satisfied with the consultation if the online information was discussed during the consultation. Moreover, patient satisfaction was positively related to recall of medical information, but only in patients with whom the online information was discussed. There was no effect found on medication adherence. Results of this study demonstrate the importance of talking about online information during a consultation for improving patient outcomes. Implications for research are discussed.